Solovki Labour Camps, 1927-28 - Cherkasov, A.A. (Vostokfilm, 1928)
Start: 00:33:00, End: 01:53:00 Soviet film that represents life in Solovki as if wasn't a forced labour camp but a sanatorium. The Solovetsky Islands were the site of the first Soviet forced labour camps, the SLON (Solovetsky special purpose camp), which held mostly political prisoners. The camp functioned from 1923 to 1939.